2020
DOI: 10.1089/aid.2020.0021
|View full text |Cite
|
Sign up to set email alerts
|

Circulating HIV-1 Integrase Genotypes in Tanzania: Implication on the Introduction of Integrase Inhibitors-Based Antiretroviral Therapy Regimen

Abstract: Tanzania has recently adapted World Health Organization antiretroviral guidelines that include integrase strand transfer inhibitors (INSTIs) in the first-line regimen. However, there is lack of evidence on integrase (IN) gene polymorphisms in viral strains circulating in Tanzania. In this study, we characterize IN gene polymorphisms in viral strains circulating in Dar es Salaam, Tanzania, before introduction of INSTIs. Plasma viral RNAs were prepared from 158 HIV-1-infected subjects, including 111 treated, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…In synergy with other major mutations it reduces susceptibility to each of the INSTIs. 31 The occurrence of T97A in individuals with subtype A is similar to that in a study that reported the mutation as most prevalent in individuals with subtype A. 31 …”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In synergy with other major mutations it reduces susceptibility to each of the INSTIs. 31 The occurrence of T97A in individuals with subtype A is similar to that in a study that reported the mutation as most prevalent in individuals with subtype A. 31 …”
Section: Discussionsupporting
confidence: 75%
“… 31 The occurrence of T97A in individuals with subtype A is similar to that in a study that reported the mutation as most prevalent in individuals with subtype A. 31 …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It is imperative to monitor the presence of mutations against INSTIs that can affect treatment outcomes. Furthermore, there is limited knowledge and data available for INSTI RAMs from studies that focuses on the SSA region, where over two-thirds of the current infected individuals reside (30,31). Our previous studies found low level of RAMSs against INSTIs (21).…”
Section: Discussionmentioning
confidence: 94%
“…Notably, increasing multi-class acquired drug resistance has been widely reported [ 10 , 11 , 22 , 23 ], as well as increasing NNRTI resistance amongst newly-diagnosed infants [ 24 ], showing the growing burden of drug resistance. Newer drugs in the class integrase strand transfer inhibitors (INSTI) such as dolutegravir have had very low to no drug resistance [ 25 ]. Nevertheless, suboptimal adherence and virologic monitoring with limited access to routine drug resistance mutation testing may increase the chances of their resistance.…”
Section: Introductionmentioning
confidence: 99%